Coexistence of Allergic Rhinitis in Children Attending Paediatric Asthma Clinic - Singh, Rajesh Kumar; Simalti, Ashish Kumar (Journal of Nepal Paediatric Society, 2019)
Introduction: Asthma and allergic rhinitis are considered manifestations of the chronic inflammatory respiratory syndrome of the common airways or united airways disease. We conducted a prospective epidemiological study to evaluate the prevalence of allergic rhinitis among children already diagnosed as having asthma. Methods: A prospective epidemiological study was carried out during 2015 to 2016 at a tertiary care centre in North India. The severity of asthma was classified according to the Global Initiative for Asthma (GINA) report & allergic rhinitis according to Allergic Rhinitis and Its Impact on Asthma (ARIA). Results: A total of 64 children were screened. After excluding five subjects (7.8%), 59 subjects with asthma were analysed. We could not find any definitive correlation between severity of asthma to severity of allergic rhinitis (p > 0.05). The prevalence of co morbidity of asthma and allergic rhinitis was maximum when onset of asthma was between three to six years (70%), was 40% for < three years and 50% when age of onset was six to nine years. The age of onset of asthma in children having asthma only was five years and that of children with both asthma and allergic rhinitis was 5.5 years. This difference was not significant (p > 0.05). Conclusion: There was a high prevalence of co morbidity (50.84%) of allergic rhinitis among patients with asthma. A positive correlation was found between duration and severity of asthma, but this was not observed for allergic rhinitis. In most cases asthma preceded or started with AR.